IMF Research Bulletin, September 2006 - Spilimbergo, Antonio (Washington, D.C. : International Monetary Fund, 2006)
Research summaries on (1) measuring inflation, and (2) strengthening Poverty Reduction and Growth Facility (PRGF) programs through poverty and social impact analysis (PSIA); country study on Spain; listing of contents of Vol. 53, Special Issue of IMF Staff Papers, summary of recently published IMF book entitled "IMF-Supported Programs: Recent Staff Research"; listings of recent external publications by IMF staff members, IMF Working Papers, and visiting scholars at the IMF during January-August 2006.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet